Ricoeur's theory of narrative time and one hundred years of solitude - Álvarez Martínez, Luis Gustavo (Escuela de Ciencias Sociales y Humanidades, UNED, 2015)
Paul Ricoeur´s narrative theory of time proposes that we, during our reading, move backwards and forward in narrative time and that “temporality springs forth in the plural unity of future, past and present” (167) . In utilizing his theory of time and the idea of cyclical time as a prominent characteristic in twentieth century literature, I attempt to apply his intriguing theory to an exemplary novel, One Hundred Years of Solitude (1967) by the Colombian Gabriel García Márquez. The essay demonstrates how the circularity of the imaginary travel and the linearity of the quest as such are thus put together. Indeed, time is circular and recurrent rather than rectilinear and progressive in this novel wherein readers are moved between present, past and future time.